Blind source camera identification - Kharrazi, Mehdi; Sencar, H. T.; Memon, N. (2004 International Conference on Image Processing, 2004. ICIP '04, 2004)
An interesting problem in digital forensics is that given a digital image, would it be possible to identify the camera model which was used to obtain the image. In this paper we look at a simplified version of this problem by trying to distinguish between images captured by a limited number of camera models. We propose a number of features which could be used by a classifier to identify the source camera of an image in a blind manner. We also provide experimental results and show reasonable accuracy in distinguishing images from the two and five different camera models using the proposed features.